Innovation of edible coating based on sugarcane bagasse and avocado seeds with integrated moringa leaf fortification and QR code technology as fruit protection - Shufa, Nabilla Izzus; Fatimah, Ghefira Nur; Baety, Annisa Nur (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Fruits are one of the leading agricultural commodities in Indonesia, with abundant availability and high consumption rates. Improper fruit storage can cause fruits to spoil quickly and increase organic waste. Sugarcane bagasse waste is one of the largest contributors to organic waste in Indonesia's agricultural sector. On the other hand, avocado seeds are often considered waste because people generally only consume the fruit flesh and discard the seeds without utilizing them. Both types of waste have the potential to be used as biodegradable and environmentally friendly edible coatings for fruits. This scientific study aims to explain the edible coating made from sugarcane bagasse and avocado seeds fortified with moringa leaves as an innovation in addressing issues in the food industry, particularly regarding the quality of fruit flesh that easily spoils due to improper packaging. Methods: The edible coating was produced through the extraction of sugarcane bagasse, avocado seeds, and moringa leaves, followed by homogenization for coating preparation. The edible coating can then be applied to the fruit. The writing method used in this scientific work is based on literature studies from data and information obtained through books, scientific journals, and several relevant sources. Findings: The results indicate that edible coating based on sugarcane bagasse waste has the potential to maintain fruit quality because it contains approximately 40-50% cellulose, which can be used as a base material for natural biopolymers in edible coating. The addition of avocado seeds acts as an antibacterial, antioxidant, starch, and lipid to form a strong, flexible, and water-resistant edible coating structure. The addition of moringa leaves acts as a fortifier for the fruit. Conclusion: The development of edible coatings based on sugarcane bagasse waste and avocado seeds will create an innovative fruit wrapper that preserves fruit quality and is environmentally friendly. Novelty/Originality of this article: Edible coatings on the market generally focus only on the wrapping layer to protect the fruit, without considering the nutritional content of the fruit, which decreases over time. Fortifying edible coatings with moringa leaves can help maintain and enhance fruit nutrients while preventing nutrient loss due to oxidation. This innovation is integrated with barcode technology to provide information about the advantages of edible coatings based on sugarcane bagasse and avocado seeds fortified with moringa leaves.